DUKUNGAN KELUARGA DAN RESILIENSI DIRI TERHADAP PENYESUAIAN SOSIAL PADA PENYANDANG TUNA NETRA - Marida, Lisna; Ekasari, Agustina (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Physical limitations force one to continue living with all the limitations it has, just as the blind person is often depicted with a deficient figure. Disabilities that make people feel inferior, embarrassed, useless, and not confident in socializing with the environment. This study aims to determine the relationship between family support and self-resilience to social adjustment. The subject of this research is the blind person in "Tan Miyat" Bekasi which is 50 people. The sampling technique was done by purposive sampling. In this study using three measuring tools using Likert scale is the scale of family support, the scale of self-resilience, and the scale of social adjustment. The analysis was done by spearman correlation technique.  The results show that (1) there is a positive relationship between family support and social adjustment, which means that if the family support is high then the social adjustment is also high, vice versa; (2) there is a positive relationship between self-resiliency and social adjustment, which means that if self-resilience is high then social adjustment is also high, vice versa.